A Technical Assessment of Grain Storage Structures in Oyo North Senatorial District of Oyo State, Nigeria Omobowale M.O.* and Hammed Akinsoji Department of Agricultural and Environmental Engineering, University of Ibadan, (2018)
The need for updated information on storage practices by subsistence f rm rs in Oyo North Senatorial district of Oyo state, Nigeria necessitated a technical as^e^ 'men t of grain storage structures with particular interest on availability and features as well a ’ associated postharvest losses. Small-scale farmers who are not occupying government-o 'ned farm settlements were surveyed. Ten Local Government Areas, namely; Iseyin, Kajola, Iwajowa, Saki-West, Saki-East, Orelope, Irepo, Olorunsogo, Itesiwaju and Atisbo were surveyed. A total of 250 respondents, identified to be lead-farmers and storage facility owners, were interviewed using structured questionnaires. About 35.9% of respondents still mak' use of thatched rhumbu but rainfall and insect damage pose a major challenge to grains stored within. Lack of adequate design and poor maintenance culture are major causes of structu. A faaure. Efforts to reduce postharvest losses must include provision of adequate storage facilities to small-scale farmers where most crops are produced.